The abuse of polygamy in Malaysia, 2007-2009 : a critical analysis from Islamic perspective - Raudlotul Firdaus Binti Fatah Yasin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The abuse of polygamy in Malaysia is a reality that can no longer be ignored. This research is based on the theoretical assumption that the abuse has nothing to do with the Sharrah provision on polygamy, but with the human agency which has failed to apply it according to its Sharf ah general intents (maqasid al-Shari'ah) as enshrined in the Qur'an and Sunnah of the Prophet (PBUH). This is mainly a qualitative research that involves an analytical study of relevant Qur'anic verses and Prophetic traditions (ziidith) of the Prophet (PBUH) related to polygamy, and their interpretations by both classical and modern commentators. This textual analysis is aimed at determining the general intents of Sharr ah legislation on polygamy, and to identify basic qualifications that qualify Muslims to practice it. The same analytical method is applied to study a total of 220 selected polygamy application files from 2007 to 2009 available at Kuala Lumpur and Selangor Shariah Judiciary Courts. Its main objective is to determine the educational background and financial capability of the polygamy applicants, and to ascertain as to whether the "reasons for polygamy" stated in their applications are explicitly consistent with the basic qualifications and the general intents of Sharr ah legislation on polygamy. Critical analysis on IFLA (Islamic Family Law Acts) has shown that its legal provisions on polygamy and penalties on those who break the law on polygamy are inadequate to curb the abuse of polygamy. The study has also found that the majority of polygamy applicants were not equipped with the basic qualifications required by the Sharrah, and the reasons they produced in the application forms were not consistint with the general intents of Sharr ah legislation on polygamy as reflected in the Qur'an and Prophetic traditions. Based on the findings, the study demonstrates; first, the absence of basic qualifications on behalf of the applicants is one of the main causes of the abuse of polygamy; and second, many of the reasons produced by the applicants were simply concocted, uncorroborated with evidences and unjustified, and thus may lead to the abuse of polygamy. Finally, in order to address this problem, this research proposes a comprehensive reform of the administration of Islamic Family Law in Malaysia and Sharrah judicial system and the introduction of parenting course in schools and higher institutes of learning.